"Differential risk of hospitalization among single virus infections causing influenza‐like illnesses". Issue 1 (16th October 2018) - Ortiz‐Hernández, Ana A.; Nishimura, Katherine K.; Noyola, Daniel E.; Moreno‐Espinosa, Sarbelio; Gamiño, Ana; Galindo‐Fraga, Arturo; Valdéz Vázquez, Rafael; Magaña Aquino, Martín; Ramirez‐Venegas, Alejandra; Valdés Salgado, Raydel; Andrade‐Platas, Diana; Estevez‐Jimenéz, Juliana; et al.
Abstract : Background: Acute respiratory infections are a major cause of morbidity in children and are often caused by viruses. However, the relative severity of illness associated with different viruses is unclear. The objective of this study was to evaluate the risk of hospitalization from different viruses in children presenting with an influenza‐like illness (ILI). Methods: Data from children 5 years old or younger participating in an ILI natural history study from April 2010 to March 2014 was analyzed. The adjusted odds ratio for hospitalization was estimated in children with infections caused by respiratory syncytial virus (RSV), metapneumovirus, bocavirus, parainfluenza viruses, rhinovirus/enterovirus, coronavirus, adenovirus, and influenza. Results: A total of 1486 children (408 outpatients and 1078 inpatients) were included in this analysis. At least one virus was detected in 1227 (82.6%) patients. The most frequent viruses detected as single pathogens were RSV (n = 286), rhinovirus/enterovirus (n = 251), parainfluenza viruses (n = 104), and influenza A or B (n = 99). After controlling for potential confounders (age, sex, recruitment site, days from symptom onset to enrollment, and underlying illnesses), children with RSV and metapneumovirus infections showed a greater likelihood of hospitalization than those infected by parainfluenza viruses (OR 2.7 and 1.9, respectively), rhinovirus/enterovirus (OR 3.1 and 2.1, respectively), coronaviruses (OR 4.9 and 3.4, respectively), adenovirus (OR 4.6 and 3.2, respectively), and influenza (OR 6.3 and 4.4, respectively). Conclusions: Children presenting with ILI caused by RSV and metapneumovirus were at greatest risk for hospitalization, while children with rhinovirus/enterovirus, parainfluenza, coronavirus, adenovirus, and influenza were at lower risk of hospitalization.